Kaji Distribusi Temperatur Pada Peralatan Pengasapan Pisang Sale Dengan Metode Matematis Gauss Jordan - Ratna Sary; Ully Muzakir (universitas teuku umar, 2016)
The processing of “pisang sale” that exist in today's society is traditionally done by putting a banana in the embers of charcoal. Fumigation with burning in the open space takes a long time to cure the bananas which ranged from 20-24 hours with inversion every ± 4 hours.Drying equipment system consisting of a combustion chamber, heating ducts, drying cabinets and chimneys is necessary for the utilization of the heat of combustion energy can be used optimally. an equipment system that has more than one dimension is very difficult to do the heat transfer. Therefore, a numerical method of choice to resolve this case, which concerns the system with the properties of complex physical and unevenness boundary conditions. This method usually requires a lot of time, especially if it manually, but with the development of technology computerized numerically settlement is very easy and fast with computer software. The results of mathematical calculations using Gauss Jordanmodels, then the calculated temperature value obtained for T2 - T9 are respectively 95.635; 86.991; 81.338; 77.024; 73.733; 71.186; 68.819; 67,2730C.Calculation of more, complicated or complex, numerical solutions by computational methods into a very appropriate choice.So that the results can be obtained in a short time. Keywords :temperature, gauss jordan, numerical, pisang sale, heating